Comparison of the effect of ethanol and potassium iodide in antibacterial photodynamic therapy on gram negative pathogens - Topaloğlu Avşar, Nermin; Çağan, Melike; Bakay, Emel; Kolkıran, Aziz (The European Research Journal, 2021)
Objectives: Antibiotics is the most common treatment for bacterial infections. However, bacteria can change their genetic material, develop antibiotic resistance and cannot be treated. This brings the need for new treatment methods. Antibacterial Photodynamic Therapy is becoming a promising approach to treat bacterial infections. It is based on the use of photosensitizer to be activated by light with an appropriate wavelength and it will result in reactive oxygen species which are responsible for the destruction of pathogens. In this study, Antibacterial Photodynamic Therapy was examined for the treatment of Pseudomonas aeruginosa with the help of ethanol and potassium iodide. Methods: The effect of Chlorin e6-based photoinactivation was studied on Multidrug resistant P. aeruginosa upon irradiation with 655-nm diode laser. Then ethanol and potassium iodide was added to the mechanism separately to increase the efficacy of photoinactivation. After each application, serial dilution method was used for the determination of viable cells. Results: Outcomes showed that only Antibacterial Photodynamic Therapy causes a mortality rate of 75%. Addition of ethanol causes a mortality rate of 93% and addition of potassium iodide causes a mortality rate of 99.9% with less amount of Chlorin e6 and light dose. Conclusions: Chlorin-e6 based photoinactivation did not provide high mortality rate on P. aeruginosa. The use of ethanol and potassium iodide increased the effect of photoinactivation. The highest mortality rate was obtained with potassium iodide. It was understood that potassium iodide was a better concomitant agent to increase the bactericidal effect of Antibacterial Photodynamic Therapy on P. aeruginosa.